الوعد - د. يسرى وليد ابراهيم (PROSPECTIVE RESEARCHES, 2006)
The present research consists of two sections. Section One tackles the concept of "Promise" in three subsections ; the first gives its linguistic, jurisprudent, and legal definition ; the second mentions its evidence in Al-Qur'an Al- Kareem and Sunna ; the third includes the bases of promise in Islamic and legal jurisprudence and their similarities. Section two is divided into two subsections. The first talks about the effect of promise and its fulfillment. The second tackles the ways by which the promise is fulfilled in the Islamic and legal jurisprudence. Finally, the research gives a set of conclusions and recommendations.